The Effect of Anti-Smoking Advertising on Changes in Smoking Intentions in Active Smokers - Mohammad Febrian Nurrahman Harahap (International Consortium of Education and Culture Research Studies, 2020)
Intentions to smoking represents people motivation to smoke. Exposure to anti-smoking ads considered as one of the most effective way to overcoming people intentions to smoke. Current study aims to see the effect of anti-smoking ad on smoking intentions in active smokers. This experimental quantitative study using an anti-cigarette advertisement video as an intervention method. Subjects (N = 20 people) are an undergraduate student who also an active smoker, with aged range from 18-24 years old. The result of paired sample t-test hypothesis showed that there is significant difference of smoking intentions (p <0.05) before (M = 20,35; SD = 0,244) and after (M = 13,85; SD = 0,549) the intervention was given. An average difference of 6.5 indicates that anti-smoking ad exposure can be said to have a major impact to decrease individual smoking intentions. The modeling principles from social learning theory and teror management theory explain the changing in intentions that occured in this study. The implications of this research will be discussed further.